Efeito antinociceptivo de complexos de inclusão contendo b-ciclodextrina e (-)-linalol na nocicepção não inflamatória em roedores - Nascimento, Simone de Souza (2014)
( )-linalool (LIN) is a monoterpene alcohol majority in the essential oils of several aromatic species commonly found in northeastern Brazil, such as Ocimum basilicum and Cinnamomum verum. Recent studies have shown that LIN has important therapeutic properties, including its antinociceptive, anti-inflammatory and anticonvulsant. Despite the benefits described above, the LIN, such as monoterpenes generally exhibits low solubility in water, high volatility and short half-life, thus incorporation into cyclodextrins (CDs), especially β-CD, has emerged as a tool important to improve the physicochemical properties and biological isoprênico this derivative. Thus, we investigated the possible antinociceptive effects of LIN isolated and included in β-CD in chronic non-inflammatory muscle pain model, besides to the effects on the motor activity and the central action. Male Swiss mice (25-35 g) were divided into groups and subjected to induction protocols non-inflammatory nociception by injecting acid saline (pH 4; 20 μL) in the belly left of gastrocnemius muscle. Subsequently, they were treated orally (p.o.) with LIN (25 mg/kg) LIN/β-CD (25, 50 and 100 mg/kg) tramadol (TRM 4 mg/kg, i.p.) or vehicle (solution 0.9% saline), and evaluated for behavioral parameters over a period of 27 days. The animals were subjected to tests of mechanical hyperalgesia (von Frey digital), motor coordination (Rota Rod) and muscle strength (Grip Strength Metter), and to determine the possible involvement of areas of the central nervous system (CNS), the animals were treated and ninety minutes, were anesthetized, perfused, the brains extracted and cut in a cryostat. The brain sections were subjected to immunofluorescence protocol for Fos protein. The results were expressed as mean ± standard error of the mean. Differences between groups were analyzed by ANOVA test, a path followed by Bonferroni test. P values <0.05 were considered statistically significant. Treatment with LIN and LIN/β-CD showed antinociceptive activity in animal model of chronic non-inflammatory muscle hyperalgesia in mice at all doses tested, with the LIN/β-CD prolonged activity against isolated substance, confirming the possibility of significant improvement in the therapeutic action; treatment with LIN and LIN/β-CD did not induce motor incoordination or change in muscle strength. By immunofluorescence, we observed that treatment of LIN and LIN/β-CD presented action in the CNS, acting in the brain, whereas the retrosplenial cortex and periaqueductal gray central structures are strictly related to the mechanisms of pain modulatory.